Tumor size and proliferative marker geminin rather than Ki67 expression levels significantly associated with maximum uptake of 18F-deoxyglucose levels on positron emission tomography for breast cancers. - Arisa Nishimukai; Natsuko Inoue; Ayako Kira; Masashi Takeda; Koji Morimoto; Kazuhiro Araki; Kazuhiro Kitajima; Takahiro Watanabe; Seiichi Hirota; Toyomasa Katagiri; Shoji Nakamori; Kouhei Akazawa; et al. (PLoS ONE)
It has been well established that maximum standardized uptake value (SUVmax) for 18F-fluorodeoxyglucose positron-emission tomography/computed tomography (FDG PET/CT) is clinically useful for evaluating treatment efficacy as well as predicting prognosis of breast cancer patients. Although SUVmax reflects increased glucose uptake and metabolism possibly induced by activation of growth factor signaling or TP53 dysfunction, tumor characteristics of SUVmax-high breast cancers remain to be elucidated. For the present study, we used immunohistochemical staining to investigate expressions of phospho-ribosomal protein S6 (pS6, downstream molecule of phosphatidyl inositol 3-kinase/Akt/mammalian target of the rapamycin/S6K pathway) and phosphor-p44/42 mitogen-activated protein kinase (pMAPK). Expression levels of TP53 and proliferative marker geminin as well as Ki67 were also examined by means of immunostaining in 163 invasive breast cancers. Cutoff values were set at 10% for pS6, 20% for pMAPK and TP53, and 4% for geminin. The SUVmax levels were significantly higher in the pS6-positive (p = 0.0173), TP53-positive (p = 0.0207) and geminin-high cancers (p<0.0001), but there was no significant association between pMAPK expression levels and SUVmax levels. Multivariable analysis showed that a high geminin level (odds ratio: 6.497, 95% confidence interval: 2.427-19.202, p = 0.0001) and large tumor size (6.438, 2.224-20.946, p = 0.0005) were significantly and independently associated with SUVmax-high. Univariable but not multivariable analysis indicated that Ki67-high significantly correlated with SUVmax-high. Twenty of 23 (87.0%) breast cancers with tumor size >2cm and geminin-high showed SUVmax-high, while only 6 of 49 (12.2%) breast cancers ≤2cm in size and with low geminin levels were SUVmax-high. In conclusion, we could determine that breast cancers with a large tumor and a geminin-high rather than Ki67-high proliferative marker were significantly associated with high levels of SUVmax. These findings may signify that SUVmax reflects tumor characteristics with high proliferative activity but not activation of mTOR/S6K and MAPK pathways or increased glucose metabolism due to dysfunction of TP53.